Gender dynamics in rice-farming households in Vietnam: A literature review - Gallina, Ambra; Farnworth, Cathy Rozel (2016)
This literature review is part of the CCAFS program on low emission agriculture flagship of the CGIAR Research Program on Climate Change, Agriculture and Food Security. It serves as a background document to better understand gender roles and dynamics in the rice sector in Vietnam, and provides input into research activities on the gender dimensions of mitigation options such as alternate wetting and drying. An understanding of gender issues helps to both improve effective design and delivery of mitigation technologies and ensure that the benefits of mitigation technologies reach women and men equitably. This will enable mitigation technologies to contribute to livelihood resilience, gender equity, and other development objectives as well as to lowering greenhouse gas emissions.